2004
DOI: 10.1063/1.1648013
|View full text |Cite
|
Sign up to set email alerts
|

Free energy, energy, and entropy of swelling in Cs–, Na–, and Sr–montmorillonite clays

Abstract: A Monte Carlo method for grand canonical and grand isoshear ensemble simulations has been used to characterize the free energy, energy, and entropy of clay mineral swelling. The Monte Carlo approach was found to be more efficient at simulating water content fluctuations in the highly constrained clay environment than a previously developed molecular dynamics method. Swelling thermodynamics calculated for Cs-, Na-, and Sr-montmorillonite clays indicate a strong dependence of swelling on the interlayer ion ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
222
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(244 citation statements)
references
References 47 publications
20
222
1
Order By: Relevance
“…This composition produces a bilayer configuration of water molecules (as confirmed by the density profile) in the interlayer with the equilibrated d 001 − spacing equal to 14.67 ± 0.03Å, the value that falls into the experimentally determined 2W hydration state range (14.5-15.5Å) 13 and close to the calculated stable hydration state. 15,35,55 In this case, both methods predict that rotation from θ = 0°is an endothermic process accompanied by the increase in the Comparison of the density maps for the nonzero θ value (Figure 11b) and for θ = 0°(Supporting Information Figure S8) has revealed that the CO 2 distribution is affected by the Moire patterns formed by the basal surfaces. However, the distribution is less structured, 28 to be recognized as the Moire pattern like that depicted in Figure 10b for water molecules.…”
Section: Rotation Of Hydrated Clay Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This composition produces a bilayer configuration of water molecules (as confirmed by the density profile) in the interlayer with the equilibrated d 001 − spacing equal to 14.67 ± 0.03Å, the value that falls into the experimentally determined 2W hydration state range (14.5-15.5Å) 13 and close to the calculated stable hydration state. 15,35,55 In this case, both methods predict that rotation from θ = 0°is an endothermic process accompanied by the increase in the Comparison of the density maps for the nonzero θ value (Figure 11b) and for θ = 0°(Supporting Information Figure S8) has revealed that the CO 2 distribution is affected by the Moire patterns formed by the basal surfaces. However, the distribution is less structured, 28 to be recognized as the Moire pattern like that depicted in Figure 10b for water molecules.…”
Section: Rotation Of Hydrated Clay Systemsmentioning
confidence: 99%
“…That equilibrated spacing falls within the experimentally determined range of the 1W hydration state (11.5-12.5Å) 13 and corresponds to the calculated stable hydration state. 15,35,55,56 As a function of θ, Figure 7 (upper part) displays the various contributions to the relative potential energy. The figure shows that electrostatics plays the primary role in the overall increase of the relative potential energy upon rotation.…”
Section: Rotation Of Hydrated Clay Systemsmentioning
confidence: 99%
“…The unit cell formula is X Previous experimental and simulation studies have proved that Na + and Mg 2+ smectites can swell to 1 and 2 layer hydrates and in water rich environments, the 2-layer states are thermodynamically favorable over the 1-layer states (Brindley and Brown, 1980;Bérend et al, 1995;Cases et al, 1997;Whitley and Smith, 2004;Liu and Lu, 2006). Therefore, the models containing two water layers are focused on in this study.…”
Section: Systemsmentioning
confidence: 99%
“…The swelling properties of clays have been studied extensively, both experimentally (Weiss et al, 1990;Cases et al, 1992;Bérend et al, 1995;Michot et al, 2002;Rinnert et al, 2005;Trausch et al, 2006;Salles et al, 2008) and theoretically (Boek et al, 1995a,b;de Siqueira et al, 1997;Young and Smith, 2000;Hensen et al, 2001;Hensen and Smit, 2002;Whitley and Smith, 2004;Tambach et al, 2004;Liu and Lu, 2006;Smith et al, 2006;Tambach et al, 2006) and are now relatively well understood. Mooney et al 3 (1952a,b) were among the first authors to show that smectites are able to sorb up to half their mass in water and that the water sorption behavior is strongly dependent on the nature of the exchangeable cation.…”
Section: Introductionmentioning
confidence: 99%